Maturity onset diabetes mellitus: response to intensive dietary management. Issue 5978 (2nd August 1975) - Hadden, D R; Montgomery, D A; Skelly, R J; Trimble, E R; Weaver, J A; Wilson, E A; Buchanan, K D
Abstract : Analysis of the first six months of intensive dietary management of 57 maturity onset diabetics showed that a large proportion of such patients could be satisfactorily controlled without the need of either oral hypoglycaemic agents or insulin. A dietitian's assessment of the patient's adherence to the prescribed diet allowed groups of good and poor dieters to be selected. Among the poor dieters the plasma insulin and triglyceride levels were significantly increased though plasma glucose levels were not significantly higher. Dietary adherence may thus be an prognostic risk factor in this group of diabetic patients.